1997
DOI: 10.1093/ajcn/65.2.409
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aspartame as part of a multidisciplinary weight-control program on short- and long-term control of body weight

Abstract: This study investigated whether the addition of the high-intensity sweetener aspartame to a multidisciplinary weight-control program would improve weight loss and long-term control of body weight. One hundred sixty-three obese women were randomly assigned to consume or to abstain from aspartame-sweetened foods and beverages during 16 wk of a 19-wk weight-reduction program (active weight loss), a 1-y maintenance program, and a 2-y follow-up period. Women in both treatment groups lost approximately 10% of initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0
6

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(157 citation statements)
references
References 25 publications
3
148
0
6
Order By: Relevance
“…The outcome of those studies, though, does not differ overall from studies in which participants were not blinded to the intervention (e.g., 39,55) , indicating that in the context of attempted weight loss the effect of LCS is not undermined by awareness of LCS consumption. However, further research would be useful.…”
Section: Conjecture: Exposure To Sweetness Increases Desire For Sweetmentioning
confidence: 91%
“…The outcome of those studies, though, does not differ overall from studies in which participants were not blinded to the intervention (e.g., 39,55) , indicating that in the context of attempted weight loss the effect of LCS is not undermined by awareness of LCS consumption. However, further research would be useful.…”
Section: Conjecture: Exposure To Sweetness Increases Desire For Sweetmentioning
confidence: 91%
“…Long-term studies comparing the impact of sugars and intense sweeteners on energy intakes are extremely limited (Table 4) (Porikos et al, 1977;Kanders et al, 1988;Tordoff and Alleva, 1990b;Blackburn et al, 1997;Raben et al, 2002). One early study conducted in a metabolic ward over 24 days (Porikos et al, 1982) showed that male subjects increased their energy intakes, compensating for some (40%) of the missing sucrose energy.…”
Section: Clinical Studies Of Intense Sweeteners and Body Weightmentioning
confidence: 99%
“…In a later study (Blackburn et al, 1997), 163 obese women were placed on a 1500 kcal/day diet. One group was specifically encouraged to use aspartame-sweetened foods and beverages during the active weight loss phase (16 weeks), a 1-year maintenance program, and a 2-year follow-up period; the other group was asked to abstain.…”
Section: Clinical Studies Of Intense Sweeteners and Body Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…A later clinical study (Blackburn et al, 1997) recruited obese women for a multidisciplinary 17-month weight control program. A total of 163 women were randomly assigned to one of two groups, being asked either to abstain from or to freely consume aspartame-sweetened foods and beverages during the weight loss phase (16 weeks), a 1-y maintenance program, and a 2-y follow-up period.…”
Section: Control Of Body Weightmentioning
confidence: 99%